2012
DOI: 10.1111/j.1939-9162.2012.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Legislative Behavior in Romania: The Effect of the 2008 Romanian Electoral Reform

Abstract: This article analyzes the impact of electoral rules on legislators’ rate of vote defection from their party position in legislatures while accounting for how party‐leadership strength mediates this impact. To this end it looks at the effect of the 2008 Romanian electoral reform. The reform shifted the electoral system from a closed‐list proportional representation to one in which all candidates run in single‐member districts. The analysis finds that because party leaders have maintained their leverage intact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…11 A list of party-switchers can be found in Appendix F. Others have suggested that voting patterns may differ depending on the nature of the division, when it occurs within the parliamentary agenda (Bräuninger, Müller and Stecker 2016;Coman 2012), and whether a vote is recorded (Hug 2010). 12 Using the extensive division titles provided by www.theyworkforyou.com for the later period of our study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) we identify where and 12 Recent advances in the literature on roll call votes have focussed on analysing and accounting for selection effects (Carrubba, Gabel and Hug 2008;Hug 2010;Rosas, Shomer and Haptonstahl 2015).…”
Section: Data On Divisions Defections and Debatesmentioning
confidence: 99%
“…11 A list of party-switchers can be found in Appendix F. Others have suggested that voting patterns may differ depending on the nature of the division, when it occurs within the parliamentary agenda (Bräuninger, Müller and Stecker 2016;Coman 2012), and whether a vote is recorded (Hug 2010). 12 Using the extensive division titles provided by www.theyworkforyou.com for the later period of our study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) we identify where and 12 Recent advances in the literature on roll call votes have focussed on analysing and accounting for selection effects (Carrubba, Gabel and Hug 2008;Hug 2010;Rosas, Shomer and Haptonstahl 2015).…”
Section: Data On Divisions Defections and Debatesmentioning
confidence: 99%
“…I argued in line with others that aggregation of unity scores neglects valuable variance that exists at the level of disaggregated legislative votes (Coman, 2012) and that inferences from the comparison of (aggregated) scores across countries are vulnerable to country-specific selection biases (Carrubba et al, 2006;Hug, 2010). As they offer a remedy to both problems, I studied party unity in the 16 sub-national parliaments of Germany.…”
Section: Resultsmentioning
confidence: 94%
“…Policy responsiveness, measured as the degree of congruence between public opinion and policy change, has been the most commonly used yardstick for good representation in the US Congress (Hogan, 2008, p. 859). Coman (2012) finds that the Romanian deputies elected in 2008 are more likely to propose legislation than those elected in 2004. This, however, may be a function of higher responsiveness to a constituency's legislative needs, or of mere desire to appear active (see Cumberbatch, Brown, & Skelton, 1992;Franklin & Norton, 1993, p. 109;Mattson, 1995;Wiberg & Koura, 1994, p. 35).…”
Section: Effects On the Intraparty Dimensionmentioning
confidence: 95%
“…Allocation responsiveness is more common in chambers with low party discipline where individual members can ask for more funds for their districts in return for their vote (Baron, 1991). Given the relatively high level of vote discipline in the Romanian Parliament (see Coman, 2012), the allocation of funds as a means to respond to constituency needs seems odd. However, the logic behind the allocation of funds in Romania is slightly different.…”
Section: Effects On the Intraparty Dimensionmentioning
confidence: 98%